High variability in quorum quenching and growth inhibition by furanone C-30 inPseudomonas aeruginosaclinical isolates from cystic fibrosis patients - Rodolfo García‐Contreras; Berenice Peréz-Eretza; Ricardo Jasso‐Chávez; Elizabeth Lira‐Silva; Jesús Alberto Roldán-Sánchez; Abigail González‐Valdez; Gloria Soberón‐Chávez; Rafael Coria‐Jiménez; Mariano Martínez‐Vázquez; Luis David Alcaraz; Toshinari Maeda; Thomas K. Wood (2015)
Pseudomonas aeruginosa colonizes the lungs of cystic fibrosis patients causing severe damage. This bacterium is intrinsically resistant to antibiotics and shows resistance against new antimicrobials and its virulence is controlled by the quorum-sensing response. Thus, attenuating its virulence by quorum quenching instead of inhibiting its growth has been proposed to minimize resistance; however, resistance against the canonical quorum quencher furanone C-30 can be achieved by mutations leading to increased efflux. In the present work, the effect of C-30 in the attenuation of the QS-controlled virulence factors elastase and pyocyanin was investigated in 50 isolates from cystic fibrosis patients. The results demonstrate that there is a high variability in the expression of both elastase and pyocyanin and that there are many naturally resistant C-30 strains. We report that the main mechanism of C-30 resistance in these strains was not due to enhanced efflux but a lack of permeability. Moreover, C-30 strongly inhibited the growth of several of the isolates studied, thus imposing high selective pressure for the generation of resistance.